Pengembangan Kapasitas Kelembagaan Lokal dan Tingkat Realisasi Program Penataan Lingkungan Permukiman di Perkotaan - Fultanegara, Anggun Aprinasari (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Problem of slum area is a much appear in cities. It demands people to settle the problem independently, one is local institutional. This research tries to compare seven BKM, namely four BKM in Kendal and three BKM in Pekalongan. The implementation of the PLPBK program is measured from the BLM funds utilization, realization of program utilization BLM, and the amount of partnership program. Later, local institutional capacity was measured with a three-level, namely the level of individuals, groups, and organizations. Research carried out using quantitative methods, descriptive, scoring analysis, and collecting data kuisioner. Results of analysis showed the seventh BKM have done well. Nevertheless, Kebondalem Region in Kendal is the best. Furthermore, the results of the analysis indicate the capacity in seven BKM get in on class II which is good in running the PLPBK program. However, BKM which has the highest score is Kramatsari Region in Pekalongan city with a score of 4.5.